PENGEMBANGAN ALAT PERAGA OPTIK SEBAGAI MEDIA PEMBELAJARANUNTUK MENINGKATKAN KREATIVITAS SISWA - Anisa Fitri; Syifa'ul Gummah; Sukainil Ahzan; Dwi Sabda (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
This study aims to develop optical displays as learning media in optical material to increase student creativity. The stages use the 4D model as follows: define, design, develop and dissemination. However, the dissemination stage was not implemented. Data collection instruments were validation sheets, questionnaires, and observation sheets. The data obtained were analyzed using qualitative descriptive. This tool is validated by 2 experts to obtain valid categories. Teaching aids were tested on 12 students to see students' responses and obtained an average value of 3.37 'in the strongly agree category'. During the trial, the activities of students were observed by 2 observers according to the indicators of creative thinking and obtained an average of 2.95 'in the good category'. The study concluded that the props included in the category of valid, practical, and their implementation could help the formation of student creativity. Keywords: Visual optic, optical, creativity